Analyze the Layered Structure of the DC Transmission System on The Same Tower. Issue 5 (April 2020) - Maalla, Allam
Abstract: HVDC adopts the design concept of a double-circuit erection on the same tower, which can reasonably and efficiently utilize the resources of the ground electrode and the converter station, improve the transmission capacity of the unit corridor, and save valuable transmission corridors, and reduce engineering construction and maintenance costs. Different from the previous single-loop ± 500 kV DC transmission system, DC project needs to implement dual-circuit power control and full-station reactive power control to meet the requirements of the dual-circuit DC power dispatching and the dual-circuit DC transmission to the entire station AC filter.